(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The term “aspiration” is used most of the time when a decision or desire is usually out of context with reality and it is appropriately (Not so appropriately) determined by fantasy level, which has minimum experiential (concrete reality) component attached to it. The use of aspiration has been made indifferent field.Family influences like parental ambition, parental occupation and family status play a significant role in vocational aspiration. Parental motivation has been found to be significantly related to student’s aspiration level even when social-class, status and IQ are held constant.The parental views and expectations for their children about the future job placement and children own intellectual capacity. The personality need achievements and adjustment might be helpful in understanding vocational aspirations of the adolescents. The ambitions of parents are also important in determining the level of vocational aspirations of the students. It was expected that there would be positive relationship between ambitions of parents for their children and vocational aspiration of students.